Complexin 2 regulates secretion of immunoglobulin in antibody‐secreting cells. Issue 4 (5th November 2019) - Tsuru, Emi; Oryu, Kohei; Sawada, Ken; Nishihara, Makoto; Tsuda, Masayuki
Abstract: Introduction: Complexins (CPLXs), initially identified in neuronal presynaptic terminals, are cytoplasmic proteins that interact with the soluble N ‐ethylmaleimide‐sensitive factor attachment protein receptors (SNARE) complex to regulate the fusion of vesicles to the plasma membrane. Although much is known about CPLX function in neuronal synaptic vesicle exocytosis, their distribution and role in immune cells are still unclear. In this study, we investigated CPLX2 knockout (KO) mice to reveal the role of CPLXs in exocytosis of lymphocytes. Methods: We examined the expression of CPLXs and SNAREs in lymphocytes. To study the effect of CPLXs on the immune system in vivo, we analyzed the immune phenotype of CPLX2 KO mice. Furthermore, antibodies secretion from the peritoneal cavity, spleen, and bone marrow cells of wild‐type (WT) and CPLX2 KO mice were determined. Results: CPLX2 was detected in B cells but not in T cells, while other CPLXs and SNAREs were expressed at a similar level in both B and T cells. To clarify the function of CPLX2 in B lymphocytes, serum concentrations of immunoglobulin G (IgG), IgA, IgM, and IgE were measured in WT and CPLX2 KO mice using enzyme‐linked immunosorbent assay. The level of IgM, which mainly consists of natural antibodies, was higher in KO mice than that in WT mice, while the levels of other antibodies were similar in both types of mice. Additionally, we found that spontaneous secretion of IgM and IgG1 was enhanced from the splenic antibody‐secreting cells (ASCs) of CPLX2 KO mice. Conclusion: Our data suggest that CPLX2 inhibits spontaneous secretion of IgM and IgG1 from splenic ASCs. This study provides new insight into the mechanism of antibody secretion of ASCs. Abstract : We have examined the expression of complexins (CPLXs) in mouse lymphocytes and found that CPLX2 is specifically expressed in B cells. We further explored the likely role of CPLX2 in B cells. Our observations suggest that CPLX2 plays an important role in regulating the secretion of immunoglobulin in antibody‐secreting cells